Fast and sensitive analysis of beta blockers by ultra-high-performance liquid chromatography coupled with ultra-high-resolution TOF mass spectrometry - Tomková, Jana; Ondra, Peter; Kocianová, Eva; Václavík, Jan (BMC. Biomedical chromatography, 2017)
This paper presents a method for the determination of acebutolol, betaxolol, bisoprolol, metoprolol, nebivolol and sotalol in human serum by liquid-liquid extraction and ultra-high-performance liquid chromatography coupled with ultra-high-resolution TOF mass spectrometry. After liquid-liquid extraction, beta blockers were separated on a reverse-phase analytical column (Acclaim RS 120; 100 × 2.1 mm, 2.2 μm). The total run time was 6 min for each sample. Linearity, limit of detection, limit of quantification, matrix effects, specificity, precision, accuracy, recovery and sample stability were evaluated. The method was successfully applied to the therapeutic drug monitoring of 108 patients with hypertension. This method was also used for determination of beta blockers in 33 intoxicated patients.
Keywords: Reference Standards; Female; beta blokátory; ženské pohlaví; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; lidé; hmotnostní spektrometrie; reprodukovatelnost výsledků; limita detekce; referenční standardy; Chromatography, High Pressure Liquid; Male; Mass Spectrometry; Adrenergic beta-Antagonists; Limit of Detection; lidé středního věku; mužské pohlaví; Middle Aged; Humans